Long non-coding RNA Panel on Prognosis of Glioma in Iranian Patients - Esmaeili, Sara; Kazerani, Mahsa; Arjmandrad, Elham; Pourzarin, Amin; Falahati, Alimohammad; Khosravani, Amin; Sarli, Abdolazim; Ashoori, Hasan (Asian Pacific Journal of Cancer Biology, 2023)
Objective: Glioma is one of the most malignant brain tumors, accounting for about half of the gliomas that occur in central nervous system (CNS), originates from the glial tissue of the brain. The aim of the present study was to determine the expression levels of 3 lncRNAs (AGAP2-AS1, LINC01446 and HOTAIRM1) in patients with high grade glioma in comparison with low grade glioma. Methods: Case group consisted of 70 high grade glioma patients control group consisted of 70 patients affected with low grade glioma. RNA extraction was performed using a RNA extraction kit. Result: Our results showed that the expression of AGAP2-AS1 and LINC01446 genes significantly increased with increasing tumor grade (with fold-change ratio of 2.1 and 3.8 respectively). Also the expression of HOTAIRM1 gene increased with increasing tumor grade but this increase was not statistically significant (P value=0.6). Conclusion: We concluded that AGAP2-AS1 and LINC01446 are promising lncRNA markers in prognosis of glioma.